Assessment of ecosystem health based on landscape pattern in ecologically fragile regions at different spatial scales: A case study of Dianchi Lake basin, China - Lei, Dongmei; Zhang, Yuan; Ran, Yuju; Gao, Liping; Li, Jie; Li, Zhiguo; Mo, Jinxiao; Liu, Xuan (Frontiers in Environmental Science, 2023)
Under the background of urbanization, maintaining ecosystem health in ecologically fragile areas is an inevitable requirement for sustainable development in the future, but the ecological health status varies greatly at different spatial scales. Determining the appropriate spatial scale of ecological health assessment is the basis and premise of ecological management and environmental protection policy making. Taking Dianchi Lake basin as the research area, based on the vigor-organization-resilience (VOR) model and landscape pattern index, this study established an assessment system of ecological health to evaluate the ecosystem health status from quadrat, ecological and administrative scales, with the aim to determine a reasonable evaluation scale and strengthen regional sustainability. The results show that: (1) The suitable spatial grain of landscape pattern analysis in Dianchi Lake basin is 150 m. (2) The average values of ecosystem health indices at quadrat scale, ecological scale and administrative scale are 0.5466, 0.4977 and 0.5373, respectively, demonstrating a sub-health state. (3) The most suitable scale for ecological health assessment of Dianchi Lake basin is ecological scale, because taking sub-watershed as ecological unit can ensure the integrity of the evaluated ecosystem to the greatest extent. Multiscale assessment is helpful for ecological and environmental management departments to understand the health status of ecosystem at different scales and provide a scientific basis for regional ecological and environmental management decisions.